Improving Coastal Communities' Micro Enterprises' Knowledge Capabilities: Boosting Finance Digitalisation In Small Islands Region - Teniwut, Roberto Mario Kabi (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2025)
Central government efforts to push MSMEs (micro, small and medium enterprises) into more digitalisation to improve the effectiveness and efficiency of MSME business processes and operations may face significant challenges for MSMEs in small island regions. Internet access, ICT (information communication technology) capabilities, and fintech services penetration hamper the government's good intentions. To help the government initiative, this study aimed to improve knowledge capabilities, especially in using financial technology (fintech) by the coastal communities' micro enterprises, consisting of fishermen and marine farmers in Kei Islands, Indonesia. This study integrates SWOT analysis and Fuzzy AHP (analytical hierarchy process) to obtain a viable alternative to increase and improve the knowledge capabilities of fishermen and marine farmers who use fintech services to improve their overall managerial performance. This study uses qualitative data collected from in-depth interviews conducted on three categories of experts, namely bank and financial senior officers (one head of state-owned bank regional chief), MSMEs in fisheries (ten MSMEs), and researchers (one researcher). The result showed that more socialisation, either to increase the knowledge on fintech services available, the use of ICT, and the importance of managing the business properly, can improve the knowledge capabilities of micro enterprises in coastal areas in order to adopt business digitalisation.